Analysis of Student Competencies through Accounting Technician Certification in the Global Economy - Kusumawati, Fariyana; Sambharakreshna, Yudhanta; Wulandari, Anis (AIBPM Publisher, 2023)
This research aims to develop student competency through accounting technician certification in facing the global economy. This type of research is quantitative using a descriptive approach. Through this approach, it is hoped that it will be able to provide understanding for researchers to describe student competencies through accounting technician certification to face the global economy. The population and research sample used were active students majoring in accounting, FEB, Trunojoyo University, Madura, fourth semester and above. The results of this research state that student competency is supported by the accounting study program through practicum/training activities as well as the resources available which include facilities and infrastructure, instructor competency, learning methods, implementation of competency certification tests, usefulness of competency certification and student interest/motivation to take part. Competency certification has high potential in increasing the competency of students majoring in accounting to face the global economy.